PRELIMINARY ASSESSMENT OF THE EFFICIENCY OF A HYBRID WIND-SOLAR SYSTEM FUNCTIONING TO PROVIDE THE OWN NEEDS OF THE LOCAL CONSUMER - ШВЕДЧИКОВА, І. О.; ПІСОЦЬКИЙ, А. В. (Technologies and Engineering, 2023)
Purpose. A preliminary assessment of the efficiency characteristics of the functioning of a hybrid solar-wind system designed to meet the self-consumption needs of a local consumer, assuming the inability to generate surplus energy from renewable sources to the grid. Methodology. Based on the use of analytical methods of statistical data processing, which enable a detailed analysis and interpretation of the obtained results. Findings. The calculations of efficiency indicators have been carried out - the cost reduction coefficient and the self-sufficiency ratio for a conditional local facility with a specified load connected to the grid. Based on the calculation results, the choice of location for placing a hybrid system with renewable energy sources has been justified. An analysis of periods with high and low renewable energy generation in the specified location has been conducted to determine rational equipment parameters and strategies for energy flows managing for maximum self-sufficiency of the local consumer. Originality. It has been established that during the planning of hybrid system, it is possible preliminary to assess the efficiency indicators for a simplified configuration of a hybrid system that does not involve the use of energy storage devices. Practical value. The paper provides recommendations for evaluating the efficiency of hybrid solar-wind systems at the initial stages of system development. It is shown that assessing the loss reduction coefficient based on the average monthly generation of renewable energy sources, averaged over a multi-year period, can lead to the incorrect result (inflated values of the indicators). For more accurate assessments, it is recommended to calculate efficiency indicators using hourly values of renewable energy generation.